Assessment of heavy metal pollution in sediments from the urban section of Yihe River, Linyi City, China - Qinghai Deng; Guizong Sun; Fuquan Li; Lei Guo; Dan Shi; Liping Zhang; Zhenzhou Sun; Jingjing Yang (PLoS ONE, 2025)
The Yihe River is the largest mountain torrent river in Shandong Province, which plays an important role in flood control, irrigation and climate regulation. Due to the impacts of the upstream and urban domestic sewage, as well as industrial and agricultural wastewater, the Linyi City section of the Yihe River is expected to have a high risk of metal pollution. Sediments are the main reservoir and potential release source of metals (metalloid) in river systems. Assessment of metals in sediments can identify anthropogenic pollution. In this study, 25 sediment samples were collected from the Linyi City section of the Yihe River and its tributaries, and the concentration of As, Cd, Cr, Cu, Ni, Pb and Zn were quantified by inductively coupled plasma mass spectrometry (ICP-MS), and the concentration of Hg was determined by atomic fluorescence spectrometry (AFS). The pollution levels were evaluated by determining the contamination factor, pollution load index, geoaccumulation index, potential ecological risk assessment and toxicity risk index. Correlation analysis and absolute principal component-multiple linear regression (APCS-MLR) were used to conduct source apportionment. Cr, Cu, Pb, Zn, Ni, Cd, As, and Hg were detected in all sediment samples. Overall, the concentration of metals (metalloid) in the sediments of the main stream of the Yihe River is mostly within the environmental background value, and the overall state is from no pollution to slightly polluted, while the tributaries of the Yihe River are in a slightly polluted state. Hg and Cd are the two main metal pollutants in the surface sediments of the study area, with the average content of 1.65 and 1.11 times the background value, respectively. Most areas of the main stream of the Yihe River are free of metal pollution, with low ecological risk and no toxicity risk. The ecological risks in the tributaries (Suhe River, Benghe River, Liuqinghe River) and the river center island (Yihe River North Island) are high and assessed as presenting low toxicity. Source analysis showed that Cr, Ni, Cu, Zn, and As mainly come from natural sources and agricultural activities, while Cd, Pb, and Hg are mainly the result of transportation and industry. The results help us understand the distribution and pollution of metals (metalloid) in the river sediments, and also provide management support to local environmental management departments and relevant national departments.